2016
DOI: 10.1007/s11136-016-1431-2
|View full text |Cite
|
Sign up to set email alerts
|

“Life is at a standstill” Quality of life after lower extremity trauma in Malawi

Abstract: Purpose Low- and middle-income countries face a disproportionate burden of death and disability from injuries, many of which are due to road traffic accidents or falls. Lower extremity injuries in particular have implications not only for physical disabilities affecting work and school performance, but also for quality of life (QOL) of the individual. This qualitative study explores the psychosocial impact and QOL changes due to lower extremity injuries among trauma patients in central Malawi. Methods We tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 20 publications
4
30
0
Order By: Relevance
“…Semi-structured interviews of 35 patients admitted to Uganda's Mulago Hospital due to fractured lower extremities revealed anxiety over economic burden and disability from injury [18]. Interviews of 20 patients recovering from lower extremity trauma at a tertiary hospital in Malawi showed patients had missed several months of work, suffered reduced income, and were forced to sell assets (including their homes) due to lost income [19]. To our knowledge, there were two prior studies analyzing traumatic injury and orthopedic disease at KCMC.…”
Section: Discussionmentioning
confidence: 99%
“…Semi-structured interviews of 35 patients admitted to Uganda's Mulago Hospital due to fractured lower extremities revealed anxiety over economic burden and disability from injury [18]. Interviews of 20 patients recovering from lower extremity trauma at a tertiary hospital in Malawi showed patients had missed several months of work, suffered reduced income, and were forced to sell assets (including their homes) due to lost income [19]. To our knowledge, there were two prior studies analyzing traumatic injury and orthopedic disease at KCMC.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that Ugandans who suffered RTIs as well as those who presented for other emergency complaints suffered significant morbidity and mortality Similar disabilities and financial impacts to those described above were seen in a study of patients in Malawi who suffered traumatic lower extremity injury. [16] Patients described difficulty with activities of daily living leading to food insecurity, the sale of assets, and missed school-and work-days by family members. Our study expands on these findings by also quantifying the drops in household income as well as the total household impact in terms of weeks of labor needed to cover the sudden, unexpected costs.…”
Section: Discussionmentioning
confidence: 99%
“…Kohler et al reported that trauma to the lower extremities led to physical distress and ongoing social and economic costs, while injuries affecting mobility have widespread levels of injuries and economic consequences for the patient and affected family. [29] One year post injury in patients with lower extremity injury reported limitations in walking (46%), inability to return to work (22%), depression (39%), and post-traumatic stress disorder (18%). Long-lasting physical and psychological burdens may impede recovery and alter the lifestyle of patients with lower extremity injury.…”
Section: 0%)mentioning
confidence: 99%